Is rs759853 polymorphism in promoter of aldose reductase gene a risk factor for diabetic nephropathy? A meta-analysis - Cui, Wenpeng (Eur J Med Res, 2015)
BACKGROUND: So far, a number of case-control or cohort studies have been carried out to investigate the relationship between rs759853 polymorphism in the promoter of aldose reductase (AR) gene and the risk of diabetic nephropathy (DN). However, the results have generated considerable controversy. We performed this study to clarify the linkage between this gene mutation and the risk of DN. METHODS: A comprehensive literature search of electronic databases and a well-organized meta-analysis were conducted. RESULTS: Twelve comparisons and 4,735 individuals from nine published case-control or cohort studies were included finally. From none to large heterogeneity was observed, therefore, both fixed and random models were used. Significant differences were found between AR rs759853 polymorphism and susceptibility of DN from both type 1 and type 2 diabetes in all genetic models (allele contrast, OR = 1.37, CI (1.18, 1.59), P < 0.0001; additive model, OR = 1.78, CI (1.25, 2.53), P = 0.01; recessive model OR = 1.33 CI (1.08, 1.63), P = 0.008; dominant model, OR = 1.52, CI (1.26, 1.84), P < 0.0001; codominance model OR = 1.30 (1.15, 1.47), P < 0.0001). In stratified meta-analyses for type 2 diabetes by ethnicity, the significant relationship was found in allele contrast and dominant model in Caucasians, and in allele contrast and codominance model in Asians. However, data do not support the linkage between this gene mutation and the progression of DN. There was no significant publication bias. CONCLUSIONS: The evidence currently available shows that the AR rs759853 polymorphism may correlate with the susceptibility of DN. However, data do not support the association between this DNA variation and the progression of DN.